Gemeenteteologie en horisonversmelting in die Matteusevangelie: 'n bestekopname - A. G. van Aarde (Acta Theologica)
The article assesses the author’s contributions to Matthean studies over the past thirty years. It focuses on the hermeneutical principle of congeniality by means of distinguishing three horizons in Matthew’s narrative world: firstly, that of Jesus and his disciples commissioned to inclusive care for the marginalised; secondly, that of the Matthean community which is associated with the narrative role of the disciples; and thirdly that of the present-day reader who engages with both narratives. The article discusses congeniality in terms of the concept “hermeneutical circle”. The assessment of the author’s contributions consists of a comparison and debate with current trends in Matthean studies.